Innovation in Company Profit Management: Socialization of Numerical Calculation for Efficiency Improvement at PT Ajisaka - Mukhtar Adinugroho; Firman Yudianto; Teguh Herlambang; Leni Yuliana; Afib Rulyansah; Mohamad Yusak Anshori (Indonesian Journal of Cultural and Community Development, 2023)
This community service project aimed to enhance the efficiency and effectiveness of PT. AJISAKA's business management through the introduction of a sophisticated software tool for forecasting and profitability estimation. Blending management science with computational science, the project sought to facilitate informed decision-making by leveraging artificial intelligence in profitability ratio prediction. The methods employed involved the execution of Tri Dharma Perguruan Tinggi and extensive socialization of numerical calculation techniques related to the company's profit estimation. The project was well received by the company's management, with the software's potential to enhance business insight and streamline operations being widely appreciated. The result of this endeavor underscores the potential of AI in revolutionizing profitability forecasts and business management. Furthermore, it bolsters the case for technological self-sufficiency in the economic and business sectors, paving the way for future innovation and the broad adoption of artificial intelligence in business management. Highlights: Utilization of artificial intelligence for accurate profitability forecasting and enhanced business decision-making. Successful execution of Tri Dharma Perguruan Tinggi, promoting technological independence in the economic sector. Broad appreciation and potential for AI application in streamlining operations and fostering business insight. Keywords: Artificial Intelligence, Profitability Forecasting, Business Management, Technological Self-sufficiency, Numerical Calculation.